2014
DOI: 10.1155/2014/261628
|View full text |Cite
|
Sign up to set email alerts
|

Weed Control and Corn (Zea mays) Response to Planting Pattern and Herbicide Program with High Seeding Rates in North Carolina

Abstract: Effective weed control in corn (Zea mays L.) is important to optimize yield. Concern over environmental impact of atrazine and selection for glyphosate resistance has increased the need to develop alternative strategies that use herbicides other than atrazine and glyphosate and appropriate cultural practices to control weeds. Research was conducted during 2011 and 2012 to determine weed and corn response to herbicide programs containing dicamba, glufosinate, and glyphosate applied postemergence alone or with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
3
12
0
1
Order By: Relevance
“…Also, dense planting increased ears, stover and total yields by 25.07, 30.94 and 28.55 %, respectively. These results are in agreement with those reported by other investigators of them Porter et al (1997), Bavec & Bavec (2002), Widdicombe &Thelen (2002, Acciares & Zuluaga (2006), Maddonni et al (2006), Singh & Singh (2006) and Williams et al (2014). But, Abouziena et al (2008) found that the highest 100-grain weight and grain weight/ ear were recorded when maize was planted with low plant population.…”
Section: Weed Control Effectsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, dense planting increased ears, stover and total yields by 25.07, 30.94 and 28.55 %, respectively. These results are in agreement with those reported by other investigators of them Porter et al (1997), Bavec & Bavec (2002), Widdicombe &Thelen (2002, Acciares & Zuluaga (2006), Maddonni et al (2006), Singh & Singh (2006) and Williams et al (2014). But, Abouziena et al (2008) found that the highest 100-grain weight and grain weight/ ear were recorded when maize was planted with low plant population.…”
Section: Weed Control Effectsupporting
confidence: 92%
“…Also, similar significant effects were observed in shelling percentage, ears, stover and total yields per fad as well as harvest index where, they were increased significantly due to weeding without significant differences among the three weeding treatments which recorded at par higher averages than the un-weeded control. These results are in agreement with those obtained by El-Metwally et al (2001), Dalley et al (2006), Abouziena et al (2008), Ali et al (2011), Larbi et al (2013), Zhang et al (2013), Amare et al (2014), Sepahvand et al (2014), Williams et al (2014) and Abana & Godwin (2015).…”
Section: Weed Control Effectsupporting
confidence: 92%
“…Weed, diseases, and insect pests were rare at the field site in this region (Wang et al., 2018); therefore, no chemical control was used at the field site. However, considering the serious growth impact of weeds (Williams, Heiniger, Everman, & Jordan, 2014) and aiming to avoid impacts on maize root−shoot development as much as possible, any weeds that accidentally appeared on test plots were regularly inspected to ensure manual removal rapidly. In 2015, the tested maize XY335 was sown on 30 April and harvested on 15 September, and the full growth period was 138 d. In 2016, the maize was sown on 27 April and harvested on 11 September, and the full growth period was 137 d.…”
Section: Methodsmentioning
confidence: 99%
“…Although several studies show that narrow rows increase yields 3.8 to 10% (Barbieri et al, 2000; Johnson and Hoverstad, 2002; Thelen, 2006; Widdicombe and Thelen, 2002; Williams et al, 2014), some studies show no effect or a yield reduction (Farnham, 2001; Lee, 2006; Novacek et al, 2013; Van Roekel and Coulter, 2012). The most consistent yield responses (7–10%) to narrow rows have been in the north‐central United States (Johnson and Hoverstad, 2002; Porter et al, 1997; Sharratt and McWilliams, 2005; Thelen, 2006; Widdicombe and Thelen, 2002) or twin‐row irrigated wide‐row (36‐inch) systems in the southern United States (Karlen and Camp, 1985; Williams et al, 2014). However, Nielsen (1988) reported a 2.7% increase in grain yields with 15‐ compared with 30‐inch rows in Indiana.…”
Section: Modern Hybrids For Narrow‐row Corn Productionmentioning
confidence: 97%
“…. The most consistent yield responses (7-10%) to narrow rows have been in the north-central United States (Johnson and Hoverstad, 2002;Porter et al, 1997;Sharratt and McWilliams, 2005;Thelen, 2006;Widdicombe and Thelen, 2002) or twin-row irrigated wide-row (36-inch) systems in the southern United States (Karlen and Camp, 1985;Williams et al, 2014). However, Nielsen (1988) reported a 2.7% increase in grain yields with 15-compared with 30-inch rows in Indiana.…”
mentioning
confidence: 99%